2021
DOI: 10.1016/j.jneuroim.2021.577505
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab induced blood eosinophilia: A retrospective pharmacovigilance cohort study and review of the literature

Abstract: To describe frequency of natalizumab related eosinophilia and clinical symptoms of eosinophilic disease in our monocentric cohort. Methods: Comparison of clinical characteristics of 115 natalizumab treated and 116 untreated RRMS patients and review of literature. Results: 38% of natalizumab treated patients had eosinophilia, which occurred significantly more frequently compared to untreated MS patients (3%, p-value<0.001). In symptomatic patients, mean eosinophil counts were significantly higher than in asympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Some studies have followed eosinophil counts with time in aggregate (Bridel, 2015;Kaufmann, 2018;Plavina, 2017); none studied temporal profile patterns in individuals. A recent study found that natalizumab eosinophilia had an incidence of 38%, much higher compared to untreated people with MS (PwMS) (3%), and the eosinophil level was related to symptoms (Diem, 2021). The study authors emphasize that the risk factors for development of natalizumab-associated eosinophilia are unknown (Diem, 2021).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Some studies have followed eosinophil counts with time in aggregate (Bridel, 2015;Kaufmann, 2018;Plavina, 2017); none studied temporal profile patterns in individuals. A recent study found that natalizumab eosinophilia had an incidence of 38%, much higher compared to untreated people with MS (PwMS) (3%), and the eosinophil level was related to symptoms (Diem, 2021). The study authors emphasize that the risk factors for development of natalizumab-associated eosinophilia are unknown (Diem, 2021).…”
Section: Introductionmentioning
confidence: 88%
“…In some cases, natalizumab-associated eosinophilia is associated with symptomatic tissue infiltration. Pulmonary eosinophilia may present with cough, wheezing, fever, dyspnoea and/or respiratory failure with pulmonary infiltrates on lung imaging and eosinophils in bronchoalveolar lavage or transbronchial biopsy (Curto et al, 2016;Diem et al, 2021;Yasuda et al, 2019). Generalized skin eruption (Andre et al, 2010) and eosinophilic fasciitis (Bujold et al, 2014) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is rarely symptomatic, but, when symptoms do occur, these tend to occur in the first 12 months of treatment. There are only three additional reported cases of pulmonary disease in the context of eosinophilia attributed to Natalizumab [1][2][3], although one case was also associated with positive PR3 ANCA serology [2]. Cases of dermatitis [4] and fasciitis [5] have also been reported.…”
Section: Dear Sirsmentioning
confidence: 99%
“…This case highlights the importance of ongoing reporting of low frequency but potentially serious side effects in the post-marketing, surveillance phase of drug development. We recommend careful attention to the peripheral blood eosinophil count in those on treatment with Natalizumab, particularly when it exceeds 2 × 10 9 /L in the first year of treatment [1]. As with Natalizumab-induced hypersensitivity reactions, clarification of the underlying genetic susceptibility factors may permit identification of those at greater risk of symptomatic eosinophilia with the potential to improve drug safety [12].…”
Section: Dear Sirsmentioning
confidence: 99%
See 1 more Smart Citation